Macroeconomic determinants of the term structure of corporate spreads - Jun Yang (Bank of Canada, 2008)
We investigate the macroeconomic determinants of corporate spreads using a no-arbitrage technique. Structural shocks are identified by a New-Keynesian model. Treasury bonds are priced in an affine model with time-varying risk premia. Corporate bonds are priced in a reduced-form credit risk model where default risk depends on macroeconomic state variables. Using U.S. data, we find that the monetary policy shock contributes to more than 50% the corporate spread variations at different forecasting horizons. Its contribution, in general, declines with credit classes. In contrast, the aggregate supply and demand shocks contribute more to the spread variations in low credit classes than in high credit classes. In addition, they in general contribute more for longer forecasting horizons.
Keywords: E43; E44; G12; 330; Debt management; Financial markets; Interest rates; Finanzmarkt; Geldpolitik; Debt Management; Zinsstruktur; USA